Phosphorescent Cu (I) complex, preparation method thereof and application of phosphorescent Cu (I) complex in detection of aromatic amine compounds

By developing a phosphorescent Cu(I) complex and its preparation method, the existing photocatalytic materials are high in cost and complex methods for detecting aromatic amine compounds are solved, and efficient water pollution treatment and aromatic amine detection are achieved.

CN119638744AActive Publication Date: 2025-03-18CHONGQING INST FOR FOOD & DRUG CONTROL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411821282.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In the existing water pollution treatment technology, photocatalytic materials have high cost and room for improvement in treatment efficiency. At the same time, the existing methods for detecting aromatic amine compounds have problems such as long detection time, complex process and high cost.

Method used

A phosphorescent Cu(I) complex and its preparation method are developed. By adding acetonitrile, 1,4-(bisdiphenylphosphine)butane and 1,10-phenanthroline-5,6-dione to CuI powder, after stirring and reaction, a phosphorescent Cu(I) complex is obtained, and applied to photocatalytic degradation of pollutants and detection of aromatic amine compounds.

Benefits of technology

It has achieved a low cost, low toxicity and easy-to-develop phosphorescent Cu(I) complex, with good photocatalytic degradation performance and efficient aromatic amine detection ability, and can accurately detect aromatic amines at extremely low concentrations, and has high treatment efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638744A_ABST
    Figure CN119638744A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorescent Cu (I) complex as well as a preparation method and application thereof in detection of aromatic amine compounds. The phosphorescent Cu (I) ligand material is prepared by taking an organic phosphorus material 1, 4-bis (diphenylphosphine) butane, copper salt CuI and 1, 10-phenanthroline-5, 6-diketone as raw materials. The prepared phosphorescent Cu (I) ligand material has good adsorption and photodegradation effects on a methyl orange solution, and can be used for photocatalytic degradation of pollutants in water. Meanwhile, the phosphorescent Cu (I) complex also has a good detection effect on aromatic amine compounds, and fluorescence detection can still reflect spectral change under the condition that the aromatic amine concentration is 5 * 10 <-9 > mol / L.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of water pollution treatment, and in particular to a phosphorescent Cu(I) complex and a preparation method thereof, and application thereof in detecting aromatic amine compounds. Background Art

[0002] Wastewater treatment is a key environmental issue. The treatment of urban and industrial wastewater is very expensive. Chemical methods are important methods for water pollution treatment. Among them, photocatalytic degradation of organic pollutants in wastewater is a hot topic in the current water treatment research field. The existing photocatalytic materials are relatively expensive, and there is room for improvement in treatment efficiency. Therefore, the development of new materials with low cost and high treatment efficiency is of great significance to water pollution control.

[0003] In addition, aromatic amine compounds are a kind of dyestuff that is toxic and harmful to human body, and long-term contact with human body makes dyestuff easily absorbed by skin, and spreads in human body. These dyestuffs may undergo reduction reaction to decompose carcinogenic aromatic amines along with the normal metabolic reaction of human body, and change the DNA structure of human body through human body activation, causing human body lesions, inducing cancer, and the incubation period can be as long as 20 years. The method for detecting carcinogenic aromatic amine content at present mainly includes thin layer chromatography (TLC), high performance liquid chromatography-mass spectrometry (HPLC-MS), high performance liquid chromatography (HPLC), liquid chromatography-tandem mass spectrometry (LC-MS / MS), spectrophotometry, etc. These detection methods all have the problems such as long detection time, complex process, high detection cost. Therefore, it is of great significance to develop a detection method for new aromatic amine compounds. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a phosphorescent Cu(I) complex and a preparation method thereof and application thereof in detecting aromatic amine compounds.

[0005] In a first aspect, the present invention provides a method for preparing a phosphorescent Cu(I) complex, which is achieved by adopting the following technical scheme.

[0006] A method for preparing a phosphorescent Cu(I) complex comprises the following steps:

[0007] S1. Add acetonitrile to CuI powder, the mass volume ratio of CuI and acetonitrile is 0.019-0.030g / 4-6ml, and stir well;

[0008] S2. Add 1,4-(bis(diphenylphosphino)butane) to the mixture obtained in step S1, wherein the molar ratio of 1,4-(bis(diphenylphosphino)butane to CuI is 1:1, and after sufficient reaction, a turbid liquid containing a powdery precipitate is obtained;

[0009] S3. Add 1,10-phenanthroline-5,6-dione to the turbid solution obtained in step S2, wherein the molar ratio of 1,10-phenanthroline-5,6-dione to CuI is 1:1, and continue stirring to obtain a turbid solution containing a powdery precipitate;

[0010] S4. Add excess ether to the turbid solution obtained in step S3 to completely precipitate the product, filter it and dry the filtered product under low heat to obtain a phosphorescent Cu(I) complex.

[0011] Furthermore, in step S1, the stirring time is 0.5-1h.

[0012] Furthermore, in step S2, the sufficient reaction time is 1-2 hours.

[0013] Furthermore, in step S3, the stirring time is 1-2h.

[0014] Furthermore, in step S4, ether is added at room temperature and the stirring time is 5 min-30 min.

[0015] In a second aspect, the present invention provides a phosphorescent Cu(I) complex, which is realized by adopting the following technical solution.

[0016] A phosphorescent Cu(I) complex prepared by the above preparation method.

[0017] In a third aspect, the present invention provides a first use of the phosphorescent Cu(I) complex, which is achieved by adopting the following technical solution.

[0018] An application of the phosphorescent Cu(I) complex in photocatalytic degradation of pollutants.

[0019] Furthermore, the mass ratio of the phosphorescent Cu(I) complex to methyl orange is 250:1.

[0020] Furthermore, the reaction time of the phosphorescent Cu(I) complex to adsorb methyl orange is 30-120 min, and the reaction temperature is 25-40°C; under light conditions, the reaction time of the phosphorescent Cu(I) complex to degrade methyl orange is 0.5-2.5 h, and the reaction temperature is 35-50°C.

[0021] In a fourth aspect, the present invention provides a second use of the phosphorescent Cu(I) complex, which is achieved by adopting the following technical solution.

[0022] An application of the phosphorescent Cu(I) complex in detecting aromatic amine compounds.

[0023] Furthermore, the aromatic amine compounds include p-methoxyaniline, 4-bromoaniline, p-iodoaniline and 4-chloroaniline.

[0024] This application has the following beneficial effects.

[0025] (1) The phosphorescent Cu(I) complex of the present invention has low cost, low toxicity, is easy to develop, and has good product performance;

[0026] (2) The preparation method of the phosphorescent Cu(I) complex of the present invention is simple and convenient. It only requires dissolving the reactants in a suitable solvent and obtaining the target product by self-assembly in the solution.

[0027] (3) The phosphorescent Cu(I) complex prepared by the present invention has good performance in the experiment of photocatalytic degradation of pollutants. From the results of photocatalytic and degradation experiments, it can be seen that the optimal dosage of the product is 25 mg, the optimal reaction time is 2.5 h, the optimal reaction temperature is 30 ° C, and the optimal decolorization effect is 84.92%. Moreover, a high adsorption effect is achieved after 30 minutes of reaction at room temperature. Ultraviolet light has a certain enhancing effect on the photodegradation of the product. The phosphorescent Cu(I) complex of the present application is expected to be put into the field of sewage treatment;

[0028] (4) The phosphorescent Cu(I) complex prepared by the present invention has a good detection effect on the four aromatic amines. The aromatic amines can still be detected at extremely low concentrations, and the detection limit concentration is 5x10 -9 mol / L, the phosphorescent Cu(I) complex of the present application is expected to be put into the field of aromatic amine detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a physical picture of the phosphorescent Cu(I) ligand prepared by the present invention;

[0030] Figure 2 It is the infrared absorption spectrum of the phosphorescent Cu(I) ligand prepared by the present invention;

[0031] Figure 3 This is a scanning electron microscope analysis diagram of the phosphorescent Cu(I) ligand prepared by the present invention;

[0032] Figure 4 is an X-ray diffraction pattern of the phosphorescent Cu(I) ligand prepared by the present invention;

[0033] Figure 5 It is the ultraviolet absorption spectrum of the phosphorescent Cu(I) ligand prepared by the present invention;

[0034] Figure 6 It is a comparison chart of the adsorption rate of methyl orange by different amounts of phosphorescent Cu(I) ligand of the present invention (without ultraviolet light condition);

[0035] Figure 7 It is a comparison chart of the adsorption rate of methyl orange by the phosphorescent Cu(I) ligand of the present invention at different reaction times (without ultraviolet light conditions);

[0036] Figure 8 Comparison of the adsorption rate of methyl orange by the phosphorescent Cu(I) ligand of the present invention at different reaction temperatures (without UV illumination);

[0037] Fig. 9 This is a comparison chart of the decolorization rate of methyl orange by different amounts of phosphorescent Cu(I) ligands used in the present invention (under ultraviolet light conditions);

[0038] Fig.10 This is a comparison chart of the decolorization rate of methyl orange by the phosphorescent Cu(I) ligand of the present invention at different reaction times (under ultraviolet light conditions);

[0039] Fig.11 This is a comparison chart of the decolorization rate of methyl orange by the phosphorescent Cu(I) ligand of the present invention at different reaction temperatures (under ultraviolet light conditions);

[0040] Fig.12 The fluorescence spectra of the mixed solution of 4-chloroaniline with different concentrations and a certain concentration of the product of the present invention (where A. concentration is 5×10 -4 mol / L product solution; B1. The concentration of 4-chloroaniline in the mixed solution is 1×10 -4 mol / L; B2. The concentration of 4-chloroaniline in the mixed solution is 5×10 -5 mol / L; B3. The concentration of 4-chloroaniline in the mixed solution is 1×10 -5 mol / L; B4. The concentration of 4-chloroaniline in the mixed solution is 5×10 -6 mol / L);

[0041] Fig.13 The fluorescence spectra of the mixed solution of 4-chloroaniline with different concentrations and a certain concentration of the product of the present invention (where A. concentration is 5×10 -4 mol / L product solution; B5. The concentration of 4-chloroaniline in the mixed solution is 5×10 -7 mol / L; B6. The concentration of 4-chloroaniline in the mixed solution is 5×10 -8 mol / L; B7. The concentration of 4-chloroaniline in the mixed solution is 5×10 -9 mol / L);

[0042] Fig.14 The fluorescence spectra of the mixed solution of different concentrations of p-methoxyaniline and a certain concentration of the product of the present invention (where A. concentration is 5×10 -4 mol / L product solution; C1. The concentration of p-methoxyaniline in the mixed solution is 1×10 -4 mol / L; C2. The concentration of p-methoxyaniline in the mixed solution is 5×10 -5 mol / L; C3. The concentration of p-methoxyaniline in the mixed solution is 1×10-5 mol / L; C4. The concentration of p-methoxyaniline in the mixed solution is 5×10 -6 mol / L);

[0043] Fig.15 The fluorescence spectra of the mixed solution of different concentrations of p-methoxyaniline and a fixed concentration of the product of the present invention (where A. concentration is 5×10 -4 mol / L product solution; C5. The concentration of p-methoxyaniline in the mixed solution is 5×10 -7 mol / L; C6. The concentration of p-methoxyaniline in the mixed solution is 5×10 -8 mol / L; C7. The concentration of p-methoxyaniline in the mixed solution is 5×10 -9 mol / L);

[0044] Fig.16 The fluorescence spectra of the mixed solution of 4-bromoaniline with different concentrations and the product with a fixed concentration (where A. concentration is 5×10 -4 mol / L product solution; D1. The concentration of 4-bromoaniline in the mixed solution is 1×10 -4 mol / L; D2. The concentration of 4-bromoaniline in the mixed solution is 5×10 -5 mol / L; D3. The concentration of 4-bromoaniline in the mixed solution is 1×10 -5 mol / L; D4. The concentration of 4-bromoaniline in the mixed solution is 5×10 -6 mol / L);

[0045] Fig.17 The fluorescence spectra of the mixed solution of 4-bromoaniline with different concentrations and the product with a fixed concentration (where A. concentration is 5×10 -4 mol / L product solution; D5. The concentration of 4-bromoaniline in the mixed solution is 5×10 -7 mol / L; D6. The concentration of 4-bromoaniline in the mixed solution is 5×10 -8 mol / L; D7. The concentration of 4-bromoaniline in the mixed solution is 5×10 -9 mol / L);

[0046] Fig.18 The fluorescence spectra of the mixed solution of different concentrations of p-iodoaniline and a fixed concentration of the product of the present invention (where A. concentration is 5×10 -4 mol / L product solution; E1. The concentration of p-iodoaniline in the mixed solution is 1×10 -4 mol / L; E2. The concentration of p-iodoaniline in the mixed solution is 5×10 -5 mol / L; E3. The concentration of p-iodoaniline in the mixed solution is 1×10 -5 mol / L; E4. The concentration of p-iodoaniline in the mixed solution is 5×10 -6mol / L);

[0047] Fig.19 The fluorescence spectra of the mixed solution of different concentrations of p-iodoaniline and a fixed concentration of the product of the present invention (where A. concentration is 5×10 -4 mol / L product solution; E5. The concentration of p-iodoaniline in the mixed solution is 5×10 -7 mol / L; E6. The concentration of p-iodoaniline in the mixed solution is 5×10 -8 mol / L; E7. The concentration of p-iodoaniline in the mixed solution is 5×10 -9 mol / L). DETAILED DESCRIPTION

[0048] The invention will be further described below with reference to the accompanying drawings and embodiments.

[0049] 1. Experimental instruments and drugs

[0050] In this application, acetonitrile is used as solvent, and CuI, 1,4-bis(diphenylphosphinobutane) and 1,10-phenanthroline-5,6-dione are used as raw materials to react and prepare phosphorescent Cu(I) complex (hereinafter referred to as "product"). Methyl orange solution is used as the degradation object, and the optimal reaction time, temperature, dosage, etc. are obtained by single factor analysis. By preparing a certain concentration of product solution and four aromatic amine compound solutions of different concentrations, the two solutions are mixed for fluorescence detection, and the effect of the product on aromatic amine compounds is analyzed according to the changes in the spectrum.

[0051] The experimental instruments used in the experiment are shown in Table 1.

[0052] The characterization instruments used in the experiment are listed in Table 2.

[0053] The drugs used in the experiment are shown in Table 3.

[0054] Table 1 Experimental instruments

[0055]

[0056] Table 2 Experimental characterization instruments

[0057]

[0058] Table 3 Chemicals used in the experiment

[0059]

[0060] 2. Experimental Methods and Results

[0061] 1. Preparation of Cu(I) ligand

[0062] The experimental steps are as follows:

[0063] (1) Accurately weigh CuI (0.0015 mol, 0.287 g) solid into a round-bottom flask using an analytical balance. Add 10 ml of acetonitrile into the flask and stir on a constant temperature heating magnetic stirrer.

[0064] (2) Use an analytical balance to accurately weigh 1,4-(bis(diphenylphosphino)butane) (0.0015 mol, 0.6397 g) and add it to the flask to allow it to react fully to obtain a turbid liquid containing a white powdery precipitate. During the process, heating can be applied appropriately to accelerate the reaction rate, but the temperature should not be too high.

[0065] (3) Accurately weigh 1,10-phenanthroline-5,6-dione (0.0015 mol, 0.3153 g) using an analytical balance and add it to the flask. Continue stirring to obtain a turbid solution containing a light yellow powdery precipitate. After the reaction is complete, turn off the heating magnetic stirrer.

[0066] (4) Add excess ether to the flask to completely precipitate the product. Dry the filtered product with a slight heat and store it in a sample tube. Figure 1 shown.

[0067] 2. Characterization of phosphorescent Cu(I) complex products

[0068] The product solid was detected and analyzed by infrared, scanning electron microscopy (SEM), X-ray diffraction (XRD) and ultraviolet absorption spectrum.

[0069] Infrared spectra such as Figure 2 As shown in the infrared absorption spectrum of the product, 3218 cm -1 、3053cm -1 、2929cm -1 The three peaks are caused by the stretching movement of hydrogen-containing groups XH, X = C, N, O. 1631cm -1 It is the frequency or combination number of the out-of-plane bending vibration of the CH of benzene derivatives, and it may also be the stretching vibration of the double bond. -1 It is the CP bond stretching vibration absorption peak. 1121cm -1 、1021cm -1 isI - .694cm -1 The peak is the out-of-plane deformation vibration absorption peak of CH on the benzene ring. -1 It is the absorption peak of Cu-P bond stretching vibration.

[0070] The scanning electron microscopy results are as follows Figure 3 As shown, it can be seen that the product is irregular granular, and some particles are clustered together, which may be due to the absorption of moisture from the air during the storage process. The rough porous structure on the surface of the product particles gives it good adsorption and catalytic properties.

[0071] The X-ray diffraction results are as follows Figure 4 As shown, it can be seen that there are obvious and good diffraction peaks at 7.398°, 12.603°, and 14.653° corresponding to ①, ②, and ③ in the figure, respectively. According to the molecular formula, it can be determined that the raw materials are successfully coordinated. The three diffraction peaks are caused by the different coordination ratios of the reaction product of CuI and 1,4-bis(diphenylphosphinobutane) and 1,10-phenanthroline-5,6-dione. The diffraction peaks appearing at other angles belong to the reactant raw materials, reaction derivatives, other impurities, etc.

[0072] The product solutions of several concentrations were tested by a three-phase UV analyzer. The UV absorption characteristics of the product are as follows: Figure 5 In the figure, A1 is 1×10 -3 mol / L product solution, A2 is 2×10 -4 mol / L product solution, A3 is 5×10 -4 mol / L product solution, A4 is 5×10 -5 mol / L product solution. Figure 5 It can be seen that the product has two obvious absorption bands, 112nm and 331nm respectively. The absorption band at 331nm belongs to the target product Cu(I) ligand. -4 The product absorption peak of mol / L is relatively obvious and smooth, so this concentration is selected as the product concentration for subsequent fluorescence detection.

[0073] 3. Photocatalytic performance test of phosphorescent Cu(I) complex products

[0074] The single factor method was used to investigate the adsorption and degradation properties of Cu(I) complex products on methyl orange solution under different temperatures, product dosages, reaction times, and with or without ultraviolet light.

[0075] Evaluation methods for photocatalytic degradation

[0076] The ultraviolet light of the ultraviolet-visible spectrophotometer was used as the light source, and the reaction temperature was room temperature. The absorbance of the methyl orange solution before and after the reaction was measured by the ultraviolet spectrophotometer at the maximum wavelength (464nm). The degradation and decolorization rate of methyl orange was calculated based on the change in the absorbance before and after the reaction. The calculation formula is:

[0077]

[0078] Where: Ao: absorbance value before reaction; At: absorbance value after reaction.

[0079] The photocatalytic reaction experiment is divided into two parts: 1. The adsorption process without UV light; 2. The photodegradation process under UV light.

[0080] 3.1 Determination of optimal conditions without light

[0081] Determination of the optimal dosage under no light conditions: Use an analytical balance to accurately weigh 5 mg, 10 mg, 15 mg, 20 mg, 25 mg, and 30 mg of the product into 6 test tubes, and add 10 ml of 10 mg / L methyl orange solution to each test tube. Shake the test tubes to mix evenly and let stand for 1 hour. Filter the mixed solution to obtain a filtrate and measure the absorbance using a UV spectrophotometer. The room temperature is 25°C.

[0082] The experimental results are as follows Figure 6 As shown by Figure 6 It can be seen that with the increase of product dosage, the adsorption rate gradually increases and reaches the maximum value at 25 mg. The adsorption rate is close to the maximum value when the dosage is 15 mg, and the adsorption rate decreases slightly at 20 mg, which may be caused by whether the added product is mixed evenly or the product particles are large and the methyl orange solution is not in sufficient contact. The adsorption rate at 25 mg and 30 mg is not much different from that at 15 mg, which can explain that in this experiment, as the product dosage increases, the effect on the adsorption rate of methyl orange solution increases first and then stabilizes. The optimal product dosage is 25 mg, and the maximum adsorption rate is 77.59%.

[0083] Determination of the best time under no light conditions: Use an analytical balance to accurately weigh 8 portions of 15 mg of the product into 8 test tubes, and add 10 ml of 10 mg / L methyl orange solution to each test tube. Shake the test tubes to mix them evenly, then let them stand and start timing. Take a test tube and filter it every 15 minutes, and measure the absorbance of the filtrate. At this time, the room temperature is 17°C.

[0084] The experimental results are as follows Figure 7 As shown by Figure 7 It can be seen that as the reaction time increases, the adsorption first increases, then shows a fluctuating trend, and reaches the maximum value at 105 minutes. During the reaction time of 30 minutes to 105 minutes, although the adsorption rate fluctuates, the adsorption rate gradually increases as a whole, and begins to decline after reaching 105 minutes. Therefore, the optimal reaction time is 105 minutes, and the maximum adsorption rate is 79.45%.

[0085] Determination of the optimal temperature under no light conditions: Use an analytical balance to accurately weigh 5 portions of 15 mg of the product into 5 test tubes, and add 10 ml of 10 mg / L methyl orange solution to each test tube. Shake the test tubes to mix them evenly, and place the test tubes in a constant temperature water bath at 30°C, 40°C, 50°C, 60°C, and 70°C, respectively. After 15 minutes, take out the test tubes and filter them, and measure the absorbance of the filtrate.

[0086] The experimental results are as follows Figure 8 As shown by Figure 8It can be seen that as the ambient temperature increases, the adsorption rate shows a gradual downward trend. Since the indoor temperature of the test reached 25°C, the initial temperature of the test was 30°C. According to the experimental data of the best dosage and the best time under the condition of no light, the adsorption rate below 30°C is less than 80%, so it can be determined that the best reaction temperature is 30°C, and the best adsorption rate is 82.72%.

[0087] 3.2 Determination of optimal conditions under UV light

[0088] The best dosage was determined under ultraviolet light. Accurately weigh 10 mg, 15 mg, 20 mg, 25 mg, and 30 mg of the product into 5 test tubes using an analytical balance. 10 ml of 10 mg / L methyl orange solution was added to each test tube. The test tubes were shaken to mix evenly and allowed to stand for 30 minutes to reach adsorption equilibrium. The test tubes were placed under ultraviolet light for 80 minutes, and then the test tubes were taken out for filtration and the absorbance of the filtrate was determined. The room temperature was 20°C at this time.

[0089] The experimental results are as follows Fig. 9 As shown by Fig. 9 It can be seen that as the amount of product increases, the decolorization rate increases first, reaches a maximum value at 25 mg, and then the decolorization rate begins to decrease. Figure 6 The data of different product dosages under no light conditions showed that the decolorization rate was improved to a certain extent, indicating that ultraviolet light promoted the degradation of methyl orange under this condition. The optimal dosage was 25 mg, and the maximum decolorization rate reached 83.38%.

[0090] The best time determination under ultraviolet light, use an analytical balance to accurately weigh 5 portions of 20mg of the product into 5 test tubes, add 10ml of 10mg / L methyl orange solution to each test tube. Shake the test tube to mix evenly, let it stand for 30min to reach adsorption equilibrium. Place the test tube under ultraviolet light, take out a test tube every 0.5h to filter, and measure the absorbance of the filtrate. At this time, the room temperature is 25.8℃.

[0091] The experimental results are as follows Fig.10 As shown by Fig.10 It can be seen that as the reaction time increases, the decolorization rate fluctuates and reaches the highest at 2.5h. It can be seen that although the data is fluctuating, the decolorization rate is at a high level and the difference is not large. It may be an error caused by uneven mixing of the product and the solution. The decolorization rate of the data with different reaction times under no light conditions is generally higher than the adsorption rate, indicating that ultraviolet light promotes the degradation of methyl orange under this condition. The optimal reaction time is 2.5h, and the maximum decolorization rate is 84.92%.

[0092] Determination of the optimal temperature under ultraviolet light: weigh 20 mg of the product accurately in a test tube using an analytical balance, and add 10 ml of a 10 mg / L methyl orange solution. Shake the test tube to mix evenly, and let it stand for 30 minutes to allow it to reach adsorption equilibrium. Place the test tube in a 30°C constant temperature water bath, illuminate it with ultraviolet light for 30 minutes, take out the test tube, filter it, and measure the absorbance of the filtrate. At this time, the room temperature is 25°C. Raise the water bath temperature by 10°C, and repeat the above steps until the water bath temperature reaches 70°C.

[0093] The experimental results are as follows Fig.11 As shown by Fig.11 It can be seen that with the increase of reaction temperature, the decolorization rate first increases and then gradually decreases, and then increases again at 70℃. Figure 8 In the data of different reaction temperatures under no light conditions, the decolorization rate under ultraviolet light at 30℃ and 40℃ is lower than the adsorption rate without light, indicating that ultraviolet light weakens the adsorption at this temperature; while the decolorization rate under ultraviolet light at 50-70℃ is greater than the adsorption rate without light, indicating that ultraviolet light in this temperature range promotes the degradation of methyl orange. The optimal reaction temperature is 40℃, and the maximum decolorization rate is 77.2%.

[0094] 4. Application of phosphorescent Cu(I) complexes in the detection of aromatic amines

[0095] The fluorescence detection was divided into two times, the first detection concentration was 5×10 -4 mol / L product solution (the solvent of the product solution is DMF), the concentration is 5×10 -4 mol / L product solution and four solutions with concentrations of 1×10 -4 mol / L、5×10 -5 mol / L、1×10 -5 mol / L、5×10 -6 mol / L of aromatic amine solution. The second test concentration was 5×10 -4 mol / L product solution, concentration of 5×10 -4 mol / L product solution and four solutions with concentrations of 5×10 -7 mol / L、5×10 -8 mol / L、5×10 -9 mol / L mixed solution of aromatic amine solution. The excitation wavelength of detection is 350nm. The four aromatic amines are: p-methoxyaniline, 4-bromoaniline, p-iodoaniline, and 4-chloroaniline.

[0096] 4.1. Phosphorescent Cu(I) complexes react with 4-chloroaniline

[0097] First test: concentration is 5×10 -4 mol / L product solution, concentration of 5×10-4 mol / L of the product and 4-chloroaniline, the concentration of 4-chloroaniline is: 1×10 -4 mol / L、5×10 -5 mol / L、1×10 -5 mol / L、5×10 - 6 mol / L, the test results are as follows Fig.12 shown.

[0098] Depend on Fig.12 It can be seen that the fluorescence intensity of the mixed solution of 4-chloroaniline and the product is greater than the fluorescence intensity of the single product in the first fluorescence detection result, indicating that 4-chloroaniline enhances the fluorescence intensity of the product. As the concentration of 4-chloroaniline gradually decreases, the fluorescence intensity of the mixed solution first decreases and then increases. It can be shown that the product has a good detection effect on 4-chloroaniline.

[0099] Second test: concentration was 5×10 -4 mol / L product solution, concentration of 5×10 -4 The product and 4-chloroaniline concentrations were 5×10 -7 mol / L、5×10 -8 mol / L、5×10 -9 mol / L mixed solution, the test results are as follows Fig.13 shown.

[0100] Depend on Fig.13 It can be seen from the second fluorescence detection result that the fluorescence intensity of the mixed solution of 4-chloroaniline and the product is still greater than the fluorescence intensity of the single product. As the concentration of 4-chloroaniline decreases, the corresponding fluorescence intensity also decreases. -9 mol / L, the fluorescence intensity of the mixed solution is very close to that of the single product solution, and the concentration is 5×10 - 9 mol / L can be used as the detection limit of product 4-chloroaniline.

[0101] 4.2. Phosphorescent Cu(I) complexes interacting with p-methoxyaniline

[0102] The first test was performed at a concentration of 5 × 10 -4 mol / L product solution, concentration of 5×10 -4 The product and p-methoxyaniline concentrations were 1×10 -4 mol / L、5×10 -5 mol / L、1×10 -5 mol / L、5×10 -6 mol / L mixed solution, the test results are as follows Fig.14 .

[0103] Depend on Fig.14 It can be seen that the fluorescence intensity of the mixed solution of p-methoxyaniline and the product is greater than the fluorescence intensity of the single product solution. As the concentration of p-methoxyaniline decreases, the fluorescence intensity of the mixed solution gradually approaches the fluorescence intensity of the single product. It can be shown that the product has a good detection effect on p-methoxyaniline, and p-methoxyaniline enhances the fluorescence intensity of the product.

[0104] The second test was performed at a concentration of 5 × 10 -4 mol / L product solution, concentration of 5×10 -4 The product and p-methoxyaniline concentrations were 5×10 -7 mol / L、5×10 -8 mol / L、5×10 -9 mol / L mixed solution, the test results are as follows Fig.15 .

[0105] Depend on Fig.15 It can be seen that the fluorescence intensity of the mixed solution of p-methoxyaniline and the product is greater than that of the single product solution. As the concentration of p-methoxyaniline decreases, the fluorescence intensity of the mixed solution first increases and then decreases. -9 mol / L, the fluorescence intensity of the mixed solution is close to that of the single product solution, and the concentration is 5×10 -9 mol / L can be used as the detection limit of product detection of p-methoxyaniline.

[0106] 4.3. Phosphorescent Cu(I) complexes react with 4-bromoaniline

[0107] The first test was performed at a concentration of 5 × 10 -4 mol / L product solution, concentration of 5×10 -4 The concentrations of the product and 4-bromoaniline were 1×10 -4 mol / L、5×10 -5 mol / L、1×10 -5 mol / L、5×10 -6 mol / L mixed solution, the test results are as follows Fig.16 .

[0108] Depend on Fig.16 It can be seen that the fluorescence intensity of the mixed solution of 4-bromoaniline and the product is greater than that of the single product solution. As the concentration of 4-bromoaniline gradually decreases, the fluorescence intensity of the mixed solution first decreases and then increases, and 1×10 -4 mol / L、1×10 -5 mol / L、5×10 -6The fluorescence intensity of the mixed solution at the three concentrations of 1.1 mol / L changed significantly, indicating that the product had a good detection effect on 4-bromoaniline, but the concentration of 4-bromoaniline was too high to obtain the detection limit, and it was necessary to further reduce the concentration of 4-bromoaniline before conducting the test.

[0109] The second test, the concentration was 5×10 -4 mol / L product solution, concentration of 5×10 -4 The concentrations of the product and 4-bromoaniline were 5×10 -7 mol / L、5×10 -8 mol / L、5×10 -9 mol / L mixed solution, the test results are as follows Fig.17 .

[0110] Depend on Fig.17 It can be seen that the fluorescence intensity of the mixed solution of 4-bromoaniline and the product is greater than that of the single product solution. As the concentration of 4-bromoaniline gradually decreases, the fluorescence intensity of the mixed solution first increases and then decreases. - 9 mol / L, the fluorescence intensity is almost the same as that of the single product solution. This indicates that 4-bromoaniline at this concentration cannot be detected, and the detection limit of product detection of 4-bromoaniline is between 5×10 -8 -5×10 -9 mol / L.

[0111] 4.4. Reaction of phosphorescent Cu(I) complexes with p-iodoaniline

[0112] The first test was performed at a concentration of 5 × 10 -4 mol / L product solution, concentration of 5×10 -4 mol / L of the product and the concentration of p-iodoaniline were 1×10 -4 mol / L、5×10 -5 mol / L、1×10 -5 mol / L、5×10 -6 mol / L mixed solution, the test results are as follows Fig.18 .

[0113] Depend on Fig.18 It can be seen that the fluorescence intensity of the mixed solution of p-iodoaniline and the product is greater than the fluorescence intensity of the single product solution. As the concentration of p-iodoaniline gradually decreases, the fluorescence intensity of the mixed solution continues to increase. This shows that the product has a good detection effect on p-iodoaniline, but the concentration of p-iodoaniline is still too high to obtain the detection limit. It is necessary to continue to reduce the concentration of p-iodoaniline before testing.

[0114] The second test, the concentration was 5×10 -4mol / L product solution, concentration of 5×10 -4 The product and p-iodoaniline concentrations were 5×10 -7 mol / L、5×10 -8 mol / L、5×10 -9 mol / L mixed solution, the test results are as follows Fig.19 .

[0115] Depend on Fig.19 It can be seen that as the concentration of p-iodoaniline decreases, the fluorescence intensity of the mixed solution decreases. -9 mol / L, the fluorescence intensity of the mixed solution was lower than that of the single product solution. This may be because the solution was left for a long time after preparation, and some of the product precipitated out of the solution, resulting in the fluorescence intensity of the mixed solution being lower than that of the single product solution. This shows that the detection limit of the product for p-iodoaniline is between 5×10 -8 -5×10 -9 mol / L.

[0116] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a phosphorescent Cu(I) complex, characterized in that: The following steps are involved: S1. Add acetonitrile to CuI powder, the mass volume ratio of CuI and acetonitrile is 0.019-0.030g / 4-6ml, and stir well; S2. Add 1,4-(bis(diphenylphosphine)butane) to the mixture obtained in step S1, wherein the molar ratio of 1,4-(bis(diphenylphosphine)butane to CuI is 1:1, and after sufficient reaction, a turbid liquid containing a powdery precipitate is obtained; S3. Add 1,10-phenanthroline-5,6-dione to the turbid solution obtained in step S2, wherein the molar ratio of 1,10-phenanthroline-5,6-dione to CuI is 1:1, and continue stirring to obtain a turbid solution containing a powdery precipitate; S4. Add excess ether to the turbid solution obtained in step S3 to completely precipitate the product, filter it and dry the filtered product under low heat to obtain a phosphorescent Cu(I) complex.

2. The method for preparing a phosphorescent Cu(I) complex according to claim 1, characterized in that: In step S1, the stirring time is 0.5-1h.

3. The method for preparing a phosphorescent Cu(I) complex according to claim 1, characterized in that: In step S2, the sufficient reaction time is 1-2 hours.

4. The method for preparing a phosphorescent Cu(I) complex according to claim 1, characterized in that: In step S3, the stirring time is 1-2h.

5. A phosphorescent Cu(I) complex prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the phosphorescent Cu(I) complex according to claim 5 in photocatalytic degradation of pollutants.

7. The use according to claim 6, characterized in that: The mass ratio of the phosphorescent Cu(I) complex to methyl orange is 250:

1.

8. The use according to claim 6, characterized in that: The reaction time of the phosphorescent Cu(I) complex to adsorb methyl orange is 30-120 minutes, and the reaction temperature is 25-40°C; under light conditions, the reaction time of the phosphorescent Cu(I) complex to degrade methyl orange is 0.5-2.5 hours, and the reaction temperature is 35-50°C.

9. Use of the phosphorescent Cu(I) complex according to claim 5 in detecting aromatic amine compounds.

10. The use according to claim 9, characterized in that: Aromatic amine compounds include p-methoxyaniline, 4-bromoaniline, p-iodoaniline, and 4-chloroaniline.

Citation Information

Patent Citations

  • Preparation method of phosphorescent Cu (I) material and product thereof

    CN115403597A